Learnability factors of AR usage performance: Validating through survey - Hafsa, Sayera; Mazlina, Abdul Majid; Tawafak, Ragad M. (IEEE, 2021)
Augmented Reality has become an important learning medium in both educational and learning domain. AR has been in use within the game technology since long. Moreover, greater prospects of AR have been seen during learning and training, specifically in the developed countries. AR has contributed in enhancing the learnability of the users. In order to understand the impact of AR usage, this work starts by preparing the list of factors that influence the learnability with the AR usage. The list of seven (7) factors were identified through Literature Review (LR) using Kolb’s Experiential Learning Theory (ELT) 1984. Survey method was used to validate the factor’s questions, Next, the validated questions were given to student and academicians for answering through another survey for factor validation. Results showed the identified factors (Motivation, Better lab experience, Enhanced Focus, Satisfaction, Enable Visualization of Invisible Concepts, Better Learning and Performance and Confidence) within the Proposed Learnability Enhancement Model (LEM). Additionally, all the questions were validated with acceptance by experts and 32 academicians through the survey 1. Also, all the factors were accepted with 94% and above acceptance rate in survey 2. The significance of identifying these AR acceptance factors for enhancement of learnability will impact better learnability and performance with AR usage, the study will continue with testing the LEM efficiency through the simulation of AR usage on the real environment in the next phase of this work.